2015
DOI: 10.5530/ptb.1.2.2
|View full text |Cite
|
Sign up to set email alerts
|

New Age Antipsychotic: Iloperidone

Abstract: Schizophreniais a heterogeneous, chronic, severe, and disabling brain disorder that has affected people throughout history. Schizophrenia is a severely debilitating psychiatric disorder observed worldwide, with a median lifetime prevalence of 0.7%-1.0%. Iloperidone possesses stronger affinity for serotonin (5-HT2A) than dopamine (D 2) receptors, and its efficacy is roughly comparable to that of other (nonclozapine) antipsychotics. In May 2009, the Food and Drug Administration approved iloperidone for the acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…In the present study, most patients were from rural area since our catchment area was predominantly rural. Shah et al 15 in contrast reported that incidence of schizophrenia was higher in urban than in rural settings. Iloperidone was assessed for long-term evaluation as it has proven efficacy, causes minimal adverse effects as well as exhibits better compliance and tolerability.…”
Section: 13mentioning
confidence: 91%
See 1 more Smart Citation
“…In the present study, most patients were from rural area since our catchment area was predominantly rural. Shah et al 15 in contrast reported that incidence of schizophrenia was higher in urban than in rural settings. Iloperidone was assessed for long-term evaluation as it has proven efficacy, causes minimal adverse effects as well as exhibits better compliance and tolerability.…”
Section: 13mentioning
confidence: 91%
“…It was obvious from our observations that iloperidone remained effective throughout and that tolerance to iloperidone did not develop even on long-term basis since upward titration of doses at intervals was not required and majority of patients were well controlled on maintenance dose. Shah et al 15 observed that between 25 and 50% of schizophrenic patients attempt suicide, and 10% eventually succeed, contributing to a mortality rate eight times greater than that of the general population. In our study, none of the patients attempted suicide, indicating iloperidone not only prevented suicidal attempts but was also fully efficacious in controlling signs and symptoms of the disease.…”
Section: 13mentioning
confidence: 99%